JAVANIZATION IN STUDENT CITY: FINDING AND PRIORITIZING IDEA TO MAINTAIN LOCAL LANGUAGE IN INDONESIA - Zakka Ugih Rizqi; Rizky Wulan Cahyaningtyas; Dhianitya Yogiari (OISAA, 2020)
The local language is one of the cultural properties that must be maintained. However, modernization can not be avoided and it causes the young generation to do not care about their own local language anymore. In Indonesia, there are already 11 extinct local languages. If there is no action to take care, it will increase the number of local language extinction. The Javanese language is one of local languages that is the most speakers in Indonesia, especially in Yogyakarta as the student city. However, the Javanese language itself is started to be left alone by the young generation. Therefore, this research is intended to give the scientific written idea to maintain Javanese language in Yogyakarta. This research is done by 2 steps of research, the first step is finding the idea by observation, literature study, and Focus Group Discussion with 3 experts. Second, prioritizing ideas to be realized using AHP with multi-expert. The result shows that there are 3 ideas that have to be realized sequentially. The first idea to be applied is ‘One day with Javanese language program’, second is the making of ‘Java café’, and the third is the selection of ‘Javanese language ambassador’.